2005
DOI: 10.1038/sj.sc.3101757
|View full text |Cite
|
Sign up to set email alerts
|

Spasticity after spinal cord injury

Abstract: Symptoms of spasticity are often experienced by individuals with spinal cord injury (SCI) following a period of spinal shock and, in many cases, these symptoms negatively affect quality of life. Despite its prevalence, spasticity as a syndrome in the SCI population is not always managed effectively. This is likely due to the fact that the syndrome can have various presentations, each with their own specific etiology. This overview summarizes the symptoms and pathophysiology of the various presentations of spas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
320
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 428 publications
(332 citation statements)
references
References 47 publications
(290 reference statements)
7
320
0
5
Order By: Relevance
“…Several authors have purported the merit of a test battery approach, similar to that of the Spinal Cord Assessment Tool for Spastic Reflexes, 26 for the refinement of current measures or development of new spasticity measures. 3,4,9,10 These new or refined measures will also need to undergo formal assessment of their reliability and validity before broad dissemination. The author's seek to engage the clinical and research community in resolving this ongoing measurement dilemma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have purported the merit of a test battery approach, similar to that of the Spinal Cord Assessment Tool for Spastic Reflexes, 26 for the refinement of current measures or development of new spasticity measures. 3,4,9,10 These new or refined measures will also need to undergo formal assessment of their reliability and validity before broad dissemination. The author's seek to engage the clinical and research community in resolving this ongoing measurement dilemma.…”
Section: Discussionmentioning
confidence: 99%
“…1 Decq (2003) suggested a modified definition of spasticity as a symptom of the upper motor neuron syndrome characterized by an exaggeration of the stretch reflex secondary to hyperexcitability of spinal reflexes. 2,3 In a recent review, the authors acknowledged 'the common clinical conundrum of the ability of clinicians to easily recognize spasticity although its quantification remains elusive'. 4 Spasticity is often categorized symptomatically as either tonic or phasic.…”
Section: Spasticitymentioning
confidence: 99%
“…A modified Ashworth scale (MAS) was used to evaluate musculoskeletal spasticity in the six muscle groups (hip, knee, ankle flexors and extensors). 6 Spasticity was evaluated by the same investigator while the patient was in a supine position using standard procedures. 13 Room temperature was maintained constant between 21 and 24 1C.…”
Section: First Visitmentioning
confidence: 99%
“…6 Spasticity commonly affects the paralyzed muscles below the level of injury and leads to contractures, impaired bed mobility and development of pressure ulcers. However, along with others, we have shown that spasticity could protect against skeletal muscle atrophy, impaired glucose tolerance and deterioration in body composition after SCI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation